Cigarette smoke alters the invariant natural killer T cell function and may inhibit anti-tumor responses - Hogan, Andrew E.; Corrigan, Michelle A.; O'Reilly, Vincent; Gaoatswe, Gadintshware; O'Connell, Jean; Doherty, Derek G.; Lynch, Lydia; O'Shea, Donal (Clinical immunology (Orlando, Fla.), 2011)
Invariant natural killer T (iNKT) cells are a minor subset of human T cells which express the invariant T cell receptor Vα24 Jα18 and recognize glycolipids presented on CD1d. Invariant NKT cells are important immune regulators and can initiate anti-tumor responses through early potent cytokine production. Studies show that iNKT cells are defective in certain cancers. Cigarette smoke contains many carcinogens and is implicated directly and indirectly in many cancers. We investigated the effects of cigarette smoke on the circulating iNKT cell number and function. We found that the iNKT cell frequency is significantly reduced in cigarette smoking subjects. Invariant NKT cells exposed to cigarette smoke extract (CSE) showed significant defects in cytokine production and the ability to kill target cells. CSE inhibits the upregulation of CD107 but not CD69 or CD56 on iNKT cells. These findings suggest that CSE has a specific effect on iNKT cell anti-tumor responses, which may contribute to the role of smoking in the development of cancer.